Editorial comments - Mary Chabeli (AOSIS, 2008)
The content of Health SA Gesondheid reflects the complexity and the depth of the health picture in Southern Africa. Health SA Gesondheid allows the reader to embark on a journey of the richness provided within the diversity of the articles presented. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.